Sociologies of interaction - Dennis, Alex; Philburn, Rob; Smith, Gregory (Cambridge, United Kingdom Polity Press, 2013)
This book provides an invaluable introduction to the theoretical foundations and practical applications of interactionist approaches to everyday life.
Pragmatism and symbolic interactionism -- Phenomenology and ethnomethodology -- Conversation analysis and the interaction order -- Status and power -- The body, health, and illness -- Work -- Deviance -- Leisure.
Includes blibliographical references and index.
Keywords: Social interaction; Sociology -- Social psychology